2016
DOI: 10.1037/xge0000226
|View full text |Cite
|
Sign up to set email alerts
|

Polluting Black space.

Abstract: Social psychologists have long demonstrated that people are stereotyped on the basis of race. Researchers have conducted extensive experimental studies on the negative stereotypes associated with Black Americans in particular. Across 4 studies, we demonstrate that the physical spaces associated with Black Americans are also subject to negative racial stereotypes. Such spaces, for example, are perceived as impoverished, crime-ridden, and dirty (Study 1). Moreover, these space-focused stereotypes can powerfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 102 publications
8
107
0
1
Order By: Relevance
“…For example, sociological work has demonstrated that stereotypes exist regarding the physical locations that different racial groups tend to occupy (Delaney, ; Sampson & Raudenbush, ). For example, recent work has documented that stereotypes about African Americans and stereotypes about African American areas are similarly (negatively) valenced (Bonam, Bergsieker, & Eberhardt, ). In the light of the current work, it is possible to hypothesize that individual differences in the endorsement of racist ideologies will likely moderate evaluations of Black space and Black objects in terms of these stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sociological work has demonstrated that stereotypes exist regarding the physical locations that different racial groups tend to occupy (Delaney, ; Sampson & Raudenbush, ). For example, recent work has documented that stereotypes about African Americans and stereotypes about African American areas are similarly (negatively) valenced (Bonam, Bergsieker, & Eberhardt, ). In the light of the current work, it is possible to hypothesize that individual differences in the endorsement of racist ideologies will likely moderate evaluations of Black space and Black objects in terms of these stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when asked to recall descriptors of Blacks, participants use the terms “ghetto Black” and “welfare Black” more frequently than they use the term “businessman Black” (Devine & Baker, ; McCabe & Brannon, ). Similarly, participants describe Whites as “educated,” “intelligent,” and “affluent” but describe Blacks as “poor” and “live in poor areas” (Bobo & Massagli, ; Bonam, Bergsieker, & Eberhardt, ; Bonam, Yantis, & Taylor, ; Katz & Braly, ). Indeed, these results suggest that traditional stereotypes about Whites resemble upper class stereotypes and traditional stereotypes associated with Blacks reflect lower class stereotypes, at least in the United States.…”
Section: An Intersectional Approach To Race and Social Classmentioning
confidence: 99%
“…Just as neighborhood space can have an identity, so too can people hold stereotypes about neighborhood space that are directly tied to the characteristics (racial/ethnic composition being the most commonly examined) of the people that live there. For example, the stereotypes that people hold about Black neighborhoods tend to be overwhelmingly negative (e.g., impoverished, crime‐ridden, ghetto, rundown) (Bonam, Bergsieker, & Eberhardt, ). In addition, individuals’ implicit biases about race and class can shape the way that they perceive neighborhood space; individuals’ perceived risk of criminal victimization is higher when they live in neighborhoods with a percentage of young African‐American men regardless of actual neighborhood crime rates (Quillian & Pager, ; ).…”
Section: Neighborhoods As Settings Of Intersectionalitymentioning
confidence: 99%
“…Not only can these biases affect how individuals perceive their neighborhoods and the neighborhoods of others, but they can also influence the value of neighborhood space and the extent to which individuals are willing to invest in and protect neighborhood space. Recent experimental work has found that individuals evaluate homes as having a lower value when they believe the owners to be Black (vs. White) and that this relationship is explained by the activation of space‐focused stereotypes of the surrounding neighborhood and a disconnection from the neighborhood (Bonam et al., ). Bonam et al.…”
Section: Neighborhoods As Settings Of Intersectionalitymentioning
confidence: 99%
See 1 more Smart Citation